PROSES BERPIKIR SISWA SMP DALAM MENYELESAIKAN MASALAH MATEMATIKA BERDASARKAN LANGKAH-LANGKAH POLYA DITINJAU DARIADVERSITY QUOTIENT - Widyastuti, Rany; Usodo, Budi; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aims of this research are to describe the thinking process of junior high school students with type of climber, camper, and quitter in solving mathematics problems based on Polya’s rule. This was a qualitative descriptive research. The subjects of this research were taken by using a combined technique of stratified sampling and purposive sampling. The subjects of this research were three 9th grade student of SMP Negeri 1 Jaten Karanganyar regency, which consists of astudent with climber’s type, a student with camper’s type, and a student with quitter’s type. The data collection in this research was conducted through questionnaires and task-based interview technique whichwereused in the subject matter of two variable linear equation system.Thedata validationtechnique used triangulationof time andreferences. The data was analyzed by usingMiles and Huberman’s concept, that was data’s reduction, data’s presentation, and conclusion. The result of this research showed that (1) climber’s student used assimilation thinking process in understanding the problem, devising a plan, carrying out the plan, and looking back the answer, (2) camper’s student used assimilation thinking process in understanding the problem, carrying out the plan, and looking back the answer, student used assimilation and accomodation thinking process in devising a plan, and (3) quitter’s student used imperfection assimilation and accomodation thinking process in understanding the problem, student didn’t use assimilation and accomodation thinking process in devising a plan, carrying out the plan, and looking back the answer.Keywords: thinking process, problem solving, Polya’s rule, Adversity Quotient (AQ)